Levator Ani Muscle Defects in Patients With Surgical Failure. Issue 2 (March 2017) - Wyman, Allison M.; Greene, Kristie A.; Bassaly, Renee; Hahn, Lindsey; Patton, Simon; Miladinovic, Branko; Hoyte, Lennox
Abstract : Introduction: The objective of the study was to use a well-described system of measuring levator ani (LA) muscle defects from magnetic resonance images to evaluate whether major defects are correlated to an increased risk of surgical failure. Methods: A retrospective cohort study performed on patients who underwent laparoscopic uterosacral ligament suspension from 2010 to 2012. Surgical failure was defined as a composite score of anatomic bulge beyond the hymen with sensation of bulge or repeat treatment of prolapse via pessary or surgery by 1-year follow-up. Levator ani muscle defects were graded by a score of 0 (no defect), 1 (<50% muscle bulk missing), 2 (>50% muscle bulk missing), or 3 (complete loss of muscle). Total score is the sum from both graded sides, with 0 classified as having no defect, 1 to 3 classified as having minor defects, and 4 to 6 classified as having major defects. Dichotomous values of LA major defects were compared against dichotomous values of surgical outcomes via a contingency table. Fisher exact test was then performed to correlate major defects to surgical success/failure. P value of less than 0.05 was considered statistically significant. Results: Sixty-six women met the inclusion criteria. Thirteen (19.6%) patients met the criteria for surgical failure at 1 year. Of the 13, 54% (7) had a major defect, and 46% (6) had a minor or no defect (odds ratio, 1.31; 95% confidence interval, 0.39–4.41; P = 0.762). Conclusions: We did not find a statistical correlation to surgical failure after a laparoscopic uterosacral ligament suspension with LA muscle defects on preoperative magnetic resonance images within this specific patient population.